Palabra de mujer - Ponzoda, Silvia Garcia (Spain, 2004)
Janata Bennuna is Morroccan, Hanan Al Shaykh Lebanese, and Nawal Saadawi Egyptian. The three of them write in their mother tongue, the Arabic language, and are all committed intellectuals who show through their books the complexity of the social reality in the Arabian world. The three of them belong to a generation marked by pan-Arabism and studied against their families' will, and although they finally gained their support, they were living in times of change. They use literature as a weapon and denounce situations which they reject.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films